Efficacy of Polymer Injection for Ischemic Mitral Regurgitation: Persistent Reduction of Mitral Regurgitation and Attenuation of Left Ventricular Remodeling - Zeng, Xin (JACC Cardiovasc Interv, 2015)
OBJECTIVES: The aim of this study was to examine the chronic effects of polyvinyl-alcohol (PVA) injection on mitral regurgitation (MR) reduction, mitral valve geometry, and left ventricular (LV) remodeling in a chronic ischemic MR sheep model. BACKGROUND: Previous studies have demonstrated acute efficacy of PVA hydrogel polymer injection into infarcted myocardium underlying the papillary muscle to relieve MR by papillary muscle repositioning. However, the chronic efficacy of PVA injection in the chronic infarction setting remains unclear. METHODS: Sixteen sheep developed chronic MR 8 weeks after induced inferoposterior myocardial infarction. Ten consecutive sheep underwent PVA injection (PVA group) and 6 sheep served as control subjects with saline injection. Epicardial 2-/3-dimensional echocardiography was performed at the baseline, chronic MR (pre-injection), and sacrifice (8 weeks after injection) stages. RESULTS: Both groups were comparable at the baseline and chronic MR stages. At sacrifice, MR decreased from moderate to trace or mild (vena contracta: 0.17 ± 0.08 cm vs. 0.56 ± 0.10 cm, p < 0.001) in the PVA group but progressed to moderate to severe in the control group. End-systolic and -diastolic volumes remained stable in the PVA group but increased significantly in the control group (both p < 0.05). At sacrifice, compared with the control group, the PVA group had significantly less left ventricular remodeling (end-systolic volume: 41.1 ± 10.4 ml vs. 55.9 ± 12.4 ml, p < 0.05), lower MR severity (vena contracta: 0.17 ± 0.08 cm vs. 0.60 ± 0.14 cm, p < 0.01), and favorable changes in mitral valve geometry. CONCLUSIONS: Polymer injection in a chronic ischemic MR model results in persistent reduction of MR and attenuation of continued left ventricular remodeling over 8 weeks of follow-up.